Dlaczego w liturgii powinien być stosowany język łaciński? - Spataro, Robertus (Vox Patrum, 2013)
The author argues that the Latin language is closely related to the sphere of the sacrum, unchanging and beautiful, and its use in the liturgy helps in the development of the culture of many nations.